Client satisfaction in outpatient unit of Hospital Sabak Bernam Selangor Darul Ehsan, 1997 - Prabakaran Soloman Dhanaraj,; Syed Aljunid, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
A cross-sectional survey of client satisfaction was done among patient above 15 years of age in the Outpatient Unit of Hospital Sabak Bernam. Information was collected using guided interview questionnaire and focus group discussion. Client satisfaction in relation to socio-demographic characteristics, physical amenities of the hospital, waiting time and treatment time, relationship of staff with patients and the competency of doctors were studied in this research. A total of 266 respondents were involved in the interview and 108 respondents in the 13 focus group discussion. The overall satisfaction was 36.9 % (n=96) among the respondents towards the service provided in Outpatient Department Hospital Sabak Bernam. There is a significant relationship between satisfaction older patient as well as Malay ethnic group. Client satisfaction is not related to the sex of patient, income of respondent, type of illness affecting the individual, frequency of attendance, distance of hospital Sabak Bernam from residence, waiting time, consultation time and time spent in the outpatient Unit Hospital Sabak Bemam. The focus group discussion shows that clients are unsatisfied with long waiting time, drug ineffectiveness, short treatment time with doctors, inadequate doctors explanation and inadequacy of specialist services